TI_GERICHTE 12.2010.63 vom 26. April 2012 , Banca - responsabilità per operazioni non autorizzate del funzionario - danno - TI Tribunale d'appello (2012)
Banca - responsabilità per operazioni non autorizzate del funzionario - danno